Classification of Anxiety Levels of IGD Patients at RSU Royal Prima Medan Using Support Vector Machine (SVM) Algorithm - Kharisma Gunanta Ginting; Nugroho Prasetyo; Al Vino Gunawan; Magdalena Sihombing; Adli Abdillah Nababan (Teknika)
The level of patient anxiety in the Emergency Department (ED) is an important indicator that affects the diagnosis and medical management process. However, the classification of anxiety levels is often hampered by data imbalance, which can reduce the accuracy of predictive models. This study aims to develop a patient anxiety level classification model in the ED using the Support Vector Machine (SVM) algorithm with the application of the Synthetic Minority Oversampling Technique (SMOTE) to address the class imbalance issue. The data used consists of 734 patient samples divided into 80% training data and 20% testing data, including physiological parameters such as systolic and diastolic blood pressure, respiratory rate, heart rate, and demographic data such as age and gender. The preprocessing process includes imputing missing values and normalizing numerical features so that the model can learn optimally. Performance evaluation shows that the use of SMOTE increases classification accuracy from 95% to 97%, as well as improving precision, recall, and F1-score metrics at almost all anxiety levels. Visualization of the relationships between numerical features also reveals significant correlation patterns between physiological variables and patient anxiety levels. The results of this study confirm the effectiveness of SMOTE in addressing data imbalance, thus producing a more accurate anxiety level classification model that can serve as an aid in clinical decision-making. Thus, the developed model has significant clinical utility potential as a diagnostic aid that can accelerate and improve the accuracy of patient management in the emergency department, thereby supporting the overall improvement of healthcare service quality.